1995
DOI: 10.1051/jp4:1995229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn on Ageing of Cu-Al-Ni-Mn-B Alloys

Abstract: The effect of post-quench ageing in the P-phase on the transformation characteristics of a set of Cu-Al-Ni alloys with Mn and B additions have been investigated by means of D S c and X-Ray diffraction. The observed behaviour show different stages which correspond to recovery of the order suppressed by quench and second phase precipitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…Although copper-based shape memory alloys are susceptible to low temperature ageing effects which can radically alter the transformation behaviour, CuAINi shape memory alloys are known to exhibit a better thermal stability than CuZnAl alloys and this characteristic makes them suitable to be used in applications above 373 K, which is the limit for the CuZnAl alloys [1, 2,3]. These alloys are more stable at high temperatures than CuZnAl alloys, raising the upper temperature limit of operation for shape memory devices, and they are claimed to be less prone to martensite stabilization [4], As a high temperature shape memory material, CuAINi alloys have attracted widespread interest; effects of heat treatment on the transformation and mechanical behaviour [5,6,7]. For the optimization of shape memory alloys and improvement of hardness, Treppmann and Hornbogen have reported that different properties have to be connected such as optimization of functional qualities and structural properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although copper-based shape memory alloys are susceptible to low temperature ageing effects which can radically alter the transformation behaviour, CuAINi shape memory alloys are known to exhibit a better thermal stability than CuZnAl alloys and this characteristic makes them suitable to be used in applications above 373 K, which is the limit for the CuZnAl alloys [1, 2,3]. These alloys are more stable at high temperatures than CuZnAl alloys, raising the upper temperature limit of operation for shape memory devices, and they are claimed to be less prone to martensite stabilization [4], As a high temperature shape memory material, CuAINi alloys have attracted widespread interest; effects of heat treatment on the transformation and mechanical behaviour [5,6,7]. For the optimization of shape memory alloys and improvement of hardness, Treppmann and Hornbogen have reported that different properties have to be connected such as optimization of functional qualities and structural properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Za slitinu CuAlNi najčešći je mikrolegirajući element titanij, koji stvara precipitate χ-faze ((Cu,Ni) 2 TiAl) koji sprječavaju porast zrna. 1,29,30 Mangan se kao legirajući element dodaje zbog povećanja duktilnosti slitina CuAlNi, te je odgovoran za nastanak β-faznog područja i poboljšanje termomehaničkih svojstva slitina s prisjetljivosti oblika. 1,16,35 Praktična primjena slitina CuAlNi ograničena je zbog slabe obradivosti i krhkosti (intergranularni lom).…”
Section: 38unclassified
“…S druge strane, njena praktična primjena je ograničena zbog teške obradljivosti i sklonosti krhkom lomu na granici zrna. [12][13][14][15][16][17] Međutim postoji niz prednosti slitine CuAlNi u odnosu na slitinu NiTi s prisjetljivosti oblika: lakše taljenje, lijevanje i kontrola kemijskog sastava, veći Youngov modul elastičnost, viša radna temperatura i, što je najvažnije, veća stabilnost dvosmjernog efekta prisjetljivosti oblika. 9,13,18 Cilj rada je pregledno prikazati najčešće upotrebljavane slitine s prisjetljivosti oblika, postupke proizvodnje te svojstva i primjenu navedenih materijala.…”
unclassified
See 1 more Smart Citation
“…Whereas the Cu-Al-Ni family of SMAs is more widely studied, here we introduce Mn as well. Mn is known to prevent brittle γ phase (Cu9Al4) formation, enabling good superelasticity [20][21][22].…”
mentioning
confidence: 99%